The Thi\E8s abattoir: from pollutant to fertilizer - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
The Thi\E8s abattoir in Senegal is no longer a source of environmental pollution. The solid waste from slaughtered animals is fermented in a tank. This produces compost and biogas, the biogas being used to provide power to the abattoir. The waste...